2019
DOI: 10.1111/dmcn.14394
|View full text |Cite
|
Sign up to set email alerts
|

Movement‐based interventions for preschool‐age children with, or at risk of, motor impairment: a systematic review

Abstract: Aim To explore the efficacy of movement‐based interventions to improve motor skills in preschool‐age children with, or at risk of, motor impairment, including those with a diagnosis of cerebral palsy, autism spectrum disorder, and developmental coordination disorder. Method Relevant electronic databases were searched for randomized or quasi‐randomized controlled trials. Outcomes were classified using domains of the International Classification of Functioning, Disability and Health: Children & Youth version. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 62 publications
(343 reference statements)
0
10
0
Order By: Relevance
“…For example, the Pathways and Resources for Engagement and Participation intervention effectively improved participation for adolescents with physical disabilities by modifying environmental barriers to a participant‐chosen activity 32 . There is little evidence available on participation interventions for preschool age children, 33 and the perceived environmental barriers and supports reported in this study may facilitate the use of similar interventions in this age group.…”
Section: Discussionmentioning
confidence: 85%
“…For example, the Pathways and Resources for Engagement and Participation intervention effectively improved participation for adolescents with physical disabilities by modifying environmental barriers to a participant‐chosen activity 32 . There is little evidence available on participation interventions for preschool age children, 33 and the perceived environmental barriers and supports reported in this study may facilitate the use of similar interventions in this age group.…”
Section: Discussionmentioning
confidence: 85%
“…The common symptoms observed in individuals with these disorders are di culties in attention, task performance, and social interaction [1]. Most studies focused on children and adolescents [14,32,34,[41][42][43][44][45][46][47][48][49][50][51], while Fang et al [38], Fragala-Pinkham et al [52], Healy et al [53], Lang et al…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The PAIS applied in the intervention arms typically consisted of two or three 30-to 60-minute sessions per week over 8-16 weeks. Three studies declared only included randomized controlled trials (RCTs) [14,47,50] and others partially included quasi-experimental designs with controlled trials [32,[41][42][43][44]48,49,51,[53][54][55][56], cohort [34], pre-and post-tests, and case-control studies [38, 45,52], and descriptive [46]. One study lacked a clear de nition of the age range of children and a discussion of risk of bias in the studies [41].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not these exercises are effective with individuals with ASD of all ages is yet to be determined. Cameron et al suggested that movement-based interventions that are effective with older children with ASD may not be effective for preschool children (Cameron et al, 2020).…”
Section: Implementing Physical Activity As An Asd Treatmentmentioning
confidence: 99%